Analysis of the Need for Pizzaluv-Math Learning Media So that Students Can Easily Learn the Limits of Trigonometric Functions - Darmayanti, Rani; In'am, Akhsanul; Afifah, Ani; Ridho'i, Anindita Verliana; Nurmaltasari, Dewi (CV. Bimbimbingan Belajar Assyfa, 2023)
This research aims to analyze the need for innovative project-based learning media, namely